Evaluating body conformation and feed efficiency characteristics in CARI-Sonali grower chicken - DAS, ANANTA KUMAR; KUMAR, SANJEEV; MISHRA, ANIL KUMAR; RAHIM, ABDUL; KOKATE, LAXMIKANT SAMBHAJI (The Indian Journal of Animal Sciences, 2016)
The investigation was aimed to evaluate body conformation and feed efficiency characteristics in CARI-Sonali grower chicken developed and maintained by the institute. Single hatched out 112 chicks were investigated. The least squares means of body weight and weight gain, shank length, keel length, breast angle, feed intake and feed conversion ratio were estimated at various age groups. Sex of the chicks had significant effect on the body weight, weight gain and shank length at sixth week of age onwards, and keel length and breast angle at eighth week onwards; male birds having higher estimates than the females throughout the age. The FCR estimates were also affected by the sex at twelfth and sixteenth week of age, male birds having better FCR than the females throughout the age. The feed intake varied among the feeding groups almost throughout the age, body weight gain at earlier age and FCR at eighth week of age. The phenotypic correlations coefficients were positive in the range of 0.3647 to 0.9062 among the intra-week body weight, breast angle, and shank and keel lengths. These might serve as base information to the breeders for chalking out breeding strategy in concerned aspect.